Nonmedical Use of Antihistaminergic Anxiolytics and Other Prescription Drugs among Persons with Opioid Dependence. (20th December 2016) - Dahlman, Disa; Abrahamsson, Tove; Kral, Alex H.; Hakansson, Anders
Abstract : Background . Nonmedical prescription drug use (NMPDU) is an increasing problem, insufficiently studied among people in opioid maintenance treatment (OMT). This study investigates the prevalence of and factors associated with NMPDU for drug classes insufficiently described in opioid-dependent populations, including antihistaminergic anxiolytics and central stimulants. Methods . Study participants were recruited at two OMT clinics in Malmo, Sweden, between October 2014 and December 2015 (N = 73 ) and interviewed about their use, motivations for use, and acquisition and administration of prescription drugs. Results . The majority of the sample reported lifetime NMPDU: 60% for benzodiazepine-like hypnotics (z-drugs), 21% for pregabalin, 19% for stimulants, and 12%–15% for antihistaminergic anxiolytics. Lower age was associated with nonmedical benzodiazepine use (Adjusted Odds Ratio = 0.89; 95% Confidence Interval = 0.82–0.97). Illicit acquisition was reported by 61% of people using z-drugs, 46% of people using pregabalin, and 38% of people using prescription stimulants, but only by 6–10% of people using antihistaminergic anxiolytics. Conclusions . The substantial nonmedical use of pregabalin, z-drugs, and prescription stimulants found in this study suggests that clinicians should prescribe these drugs with great caution. Nonmedical use of antihistaminergic anxiolytics does not seem to be a clinical issue among people in OMT in a Swedish setting, but we propose future studies to monitor their use.